Identifying suitable zones for integrated aquifer recharge and flood control in arid Qatar using GIS-based multi-criteria decision-making - Sarra Aloui (17337901) (2024)
Groundwater resources in arid regions play a vital role in meeting water demands; however, they are facing rapid depletion due to unsustainable exploitation practices, exacerbated by climate change. Floods can present a unique opportunity for restoring groundwater levels and mitigating saltwater intrusion into aquifers. The use of properly managed floodwater for aquifer recharge offers a dual advantage by maximizing the potential of floods as a valuable water resource, while minimizing their negative impacts. In this work, we applied a GIS-based Multi-Criteria Decision-Making (MCDM) method, namely the Analytic Hierarchy Process (AHP), to delineate flood susceptible zones and groundwater recharge zones in Qatar, considering several influential topographical, hydrological, environmental, and anthropological criteria. The maps of flood susceptibility and groundwater recharge potential were validated using recent flooding events and existing recharge wells data, respectively. Sensitivity analysis was conducted on both variables to further assess their accuracy. The overlay analysis of the two validated maps suggests that approximately 64% of the Qatar peninsula presents medium to excellent suitability for aquifer recharge using floodwater. The areas best suited for floodwater-based recharge intervention are the northern and coastal regions of the peninsula, while the urban areas and southwestern area are less suitable. This study provides decision-makers with spatially explicit information on areas in Qatar that can be targeted for aquifer recharge projects using floodwater as well as recommendations on technical, economic, and regulatory considerations that require additional investigation. The approach employed can be effectively applied in similar flood-prone arid regions and is adaptable to diverse contexts. Other Information Published in: Groundwater for Sustainable Development License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.gsd.2024.101137